The Role of Decorin in Autoimmune and Inflammatory Diseases - Yuanji Dong; Jixin Zhong; Lingli Dong (Journal of Immunology Research)
Decorin is an extracellular matrix protein that belongs to the family of small leucine-rich proteoglycans. As a matrix protein, the first discovered role of decorin is participating in collagen fibril formation. Many other functions of decorin in various biological processes have been subsequently identified. Decorin is involved in an extensive signaling network and can interact with other extracellular matrix components, growth factors, receptor tyrosine kinases, and various proteases. Decorin has been shown to be involved in wound repair, cell cycle, angiogenesis, tumor metastasis, and autophagy. Recent evidence indicates that it also plays a role in immune regulation and inflammatory diseases. This review summarizes the characteristics of decorin in immune and inflammatory diseases, including inflammatory bowel disease (IBD), Sjögren’s syndrome (SS), chronic obstructive pulmonary disease (COPD), IgA nephropathy, rheumatoid arthritis (RA), spondyloarthritis (SpA), osteoarthritis, multiple sclerosis (MS), idiopathic inflammatory myopathies (IIM), and systemic sclerosis (SSc) and discusses the potential role in these disorders.